Optimizing fracture resistance of endodontically treated maxillary premolars restored with preheated thermos-viscous composite post-thermocycling, a comparative study. Part I - Heba B. Abdel-Maksoud; Bassem M. Eid; Mai Hamdy; Heba M. Abdelaal (BMC, 2024)
Abstract Purpose This research aimed to investigate fracture resistance of endodontically treated maxillary premolars restored using preheated thermo-viscous and fiber-reinforced bulk fill resin composite, in vitro. Methodology Sixty sound human maxillary premolars were selected and divided randomly into 6 groups of ten teeth each (n = 10). Group 1; is the positive control with sound unprepared teeth (P), Group 2; is the negative control in which Mesio-occluso-distal (MOD) cavities were left unrestored (N), Group 3; includes the teeth restored by incremental packing with conventional nanohybrid composite (ChP), Group 4; includes teeth restored with short fiber reinforced bulk fill composite (EF), Group 5; includes teeth restored with preheated thermo-viscous bulk fill composite (VB), and Group 6; includes teeth restored using packable bulk fill composite (XF) Tested restorative materials were bonded with a universal adhesive in self-etch mode. Teeth were kept in distilled water for 24 h at 37 °C proceeded by thermocycling (5- 55 °C, 1200×). Teeth were then exposed to compressive load till fracture at a crosshead speed of 1 mm/min. One-way ANOVA followed by Tukey post-hoc test was implemented to compare between more than two groups in non-related samples. The significance level was established at α = 0.05 for both tests. Results Intact teeth significantly recorded the highest fracture resistance values among all groups. A significant difference was recorded among all the tested groups, with the EF recording the highest values, followed by the VB group then the XF group and ChP that recorded the lowest data. Negative control premolars significantly recorded the lowest fracture. Conclusions After thermocycling, endodontically treated maxillary premolars restored with pre-heated thermos-viscous composite did not exhibit an increase in fracture resistance. Notably, our findings indicate that short fiber-reinforced composite demonstrated significantly higher fracture resistance compared to other types of composites assessed in this study. This suggests the potential superiority of short fiber-reinforced composite in enhancing the overall structural integrity of endodontically treated teeth subjected to occlusal forces.